Peningkatan Kemampuan Pemahaman dan Disposisi Matematis Siswa SMA melalui Pembelajaran Kooperatif Tipe Numbered Head Together - Abubakar Abubakar; M. Ikhsan; Rahmah Johar (Universitas Syiah Kuala, 2014)
Increased capacity and disposition of students' mathematical understanding in mathematics learning is very important as it is outlined in the curriculum KTSP (2006) and reaffirmed in year 2013. The use of an appropriate learning model is expected to achieve those goals. The purpose of this study was to determine the increase comprehension and mathematical dispositions that students taught with cooperative learning model Numbered Head Together (NHT), determine whether there is a correlation between increased capacity and disposition of mathematical understanding that students taught with cooperative learning models Numbered Head Together (NHT ). This study was a quasi-experimental study with a quantitative approach, the population class X SMA Negeri 1 Sakti, Kabupaten Pidie, randomly selected sample as many as two classes: the class as a class experiment X1 and X2 class as the control class. Data were collected using a test instrument comprehension and mathematical statistic questionnaire. Data were analyzed using t test and one-way ANOVA test. Once the data is processed and analyzed it is concluded that: (1) Increasing the ability of understanding is taught using cooperative learning models Numbered Head Together (NHT) is better than being taught by conventional teaching, (2) an increase in students' mathematical dispositions are taught using learning cooperative models Numbered Head Together (NHT) better than students taught with conventional learning, (3) There is a positive correlation between an increase in the ability of students with improved mathematical understanding students' mathematical dispositions.